Association Between Kangaroo Mother Care and Stress Level of Mothers with Low Birth Weight Infants - Muliyati, Hepti; Damanik, Rizal; Roosita, Katrin (Pakistan Journal of Nutrition, 2019)
Objective: The aim of this study was to determine the association between kangaroo mother care (KMC) of low birth weight infant (LBW) and maternal stress level. Materials and Methods: Study design was a prospective cohort with 40 subjects, consisting of 20 subjects in KMC group and 20 subjects in Conventional Method of Care (CMC) group. The differences between variables were analyzed by independent sample t-test and Mann-Whitney test. Meanwhile, the correlations between variables were analyzed by chi-square test. Results: The result showed that lower maternal stress level in the fourth week was significantly correlated with KMC practice (p<0.05). Conclusion: Kangaroo mother care was an appropriate method of care for low birth weight infants to reduce postpartum maternal stress.